Guandu River Sediment Plume Space-Time Variability Characterization on Sepetiba Bay – Rio de Janeiro, SE Brazil - Barbosa dos Santos Ferreira, Caio Eduardo; Sander de Carvalho, Lino Augusto; Nunes Ramalho da Rocha, Beatriz; Valle Machado, Wilson Thadeu; Vantrepotte, Vincent (Anuário do Instituto de Geociências, 2024)
The Sepetiba Bay (Rio de Janeiro, SE Brazil) is an important coastal environment due to its ecological characteristics, extensive biodiversity, vast green area and connection to the sea, and vast socio-economic impact due to its importance to the surrounding communities and for the country. The bay receives a considerable amount of sediments through several small rivers and artificial channels along its coast, creating a “river plume” dynamic that influences its biogeochemical processes within the bay. This study analyzes a 20-year remote sensing temporal series from MODIS-Terra, combined with a semi-analytical algorithm based on wellestablished literature, to retrieve surface sediment concentration. The results reveal an inhomogeneous spatio-temporal pattern of the plume, which varies with climatological seasons. Summer and Spring present higher sediment concentrations and range, compared to Autumn and Winter. The observed patterns in the plume suggests a heterogeneous specialization that depends on the riverine inflow, which agrees with previous literature studies. Future studies should tackle both, the increase of remote sensing algorithms’ accuracy to retrieve sediment concentration and focus on plume change detection events to better understand the impact of land cover changes within the drainage basins surrounding Sepetiba Bay.